Tableau : next steps (O'Reilly Media, Inc., 2022)
Tableau is a powerful data visualization tool. With it, you can take a simple chart and filters and turn them into a dynamic powerful dashboard—or take your huge amounts of data and provide the resources that will allow end users to easily digest all of it. Join expert Christopher Gardner to find out how to put Tableau tools, such as calculations, parameters, and dashboards, to work. You’ll learn how to use Tableau methods along with simple graphic design and user interface techniques to make your dashboards and charts useful and engaging, grant your end users control while keeping them from getting lost in the weeds, and make your layouts simple to navigate and understand.